ОСНОВНЫЕ ПРОБЛЕМЫ И ОГРАНИЧЕНИЯ В РАЗВИТИИ УПРАВЛЕНИЯ ТРАНСПОРТНЫМИ УСЛУГАМИ (Marketing Journal, 2026)
AbstractThe article examines the main problems and constraints in the development oftransport service management under modern conditions. It is shown that the currentmanagement system faces infrastructural, financial, institutional, and digital barriersthat reduce the overall efficiency of the transport sector. A high concentration of  transport activity in the road segment is identified, increasing the load on the roadnetwork and raising operational costs. Despite sectoral growth and improvements inlogistics performance indicators, investment deficits, safety issues, and environmentalrisks persist. The necessity of comprehensive modernization of organizational andeconomic management mechanisms based on strategic planning, digital integration,and sustainable development principles is substantiated.Keywords: transport management, transport services, infrastructure constraints,digitalization, logistics, transport safety, sustainable development.